Accumulation and distribution of metal(loid)s in the halophytic saltmarsh shrub, Austral seablite, Suaeda australis in New South Wales, Australia. (August 2021) - Alam, Md Rushna; Tran, Thi Kim Anh; Stein, Taylor J.; Rahman, Mohammad Mahmudur; Griffin, Andrea S.; Yu, Richard Man Kit; MacFarlane, Geoff R.
Abstract: We examined the patterns of uptake and partitioning of metal(loid)s in Suaeda australis from three highly urbanised estuaries (Sydney Olympic Park, Hunter Wetlands and Lake Macquarie) in NSW, Australia. Of these, Sydney Olympic Park was found to be the most contaminated estuary in terms of combined sediment metal(loid) load, followed by Hunter Wetlands and lowest in Lake Macquarie (via PERMANOVA). Uptake in roots was greater for the essential metals Cu and Zn along with the non-essential metal Cd and the metalloid Se (root BCFs >1) and lower for Pb and As (root BCFs <1). Substantial barriers for translocation from roots to stems were identified for all metal(loid)s (stem TFs; 0.07–0.68). Conversely, unrestricted flow from stems to leaves was observed for all metal(loid)s at unity or higher (leaf TFs ≥ 1). Strong linear relationships between sediment and root for Zn and Pb were observed, indicating roots as a useful bioindicator. Graphical abstract: Highlights: Uptake and translocation of Cu. Zn, Cd, Pb, Se and As were examined. Phytostabilisation of Cu, Zn, Cd and Se in underground plants parts. Se leaf TF indicated phytoextraction efficiency of S. australis. Root tissue showed limited bioindicator utility.